Search for second order response of nuclei to isospin probes and their connection to double beta decay. (September 2020) - Cappuzzello, F.
Abstract: In order to get quantitative information on neutrino absolute mass scale from the possible measurement of the 0νββ decay half-lives, the knowledge of the Nuclear Matrix Elements (NME) involved in such transitions is mandatory. NMEs are not observables and can only be accessed by theory. However, the many-body nature of the nuclear state involved in the decay, makes this task possible only at approximate level. In this perspective, several experimental approaches have been proposed in the years in order to provide useful information to better constrain the theory. Here a short overview of the role of charge exchange reactions in this scenario is given, with particular emphasis on second order processes, known as Double Charge Exchange (DCE) reactions.